The Waqf of Nûrî Bimaristan in Aleppo in the Mid-16th Century - Çakar, Enver (Selim Hilmi Ozkan, 2024)
Aleppo has been home to many civilisations, and especially during Zangid, Ayyubid, Mamluk and Ottoman periods, many waqf works were built in the city. One of these buildings, the Bimaristan of N?r?, was built by N?r al-D?n Mahmud, one of the Zangid rulers. This hospital which was known as the Bimaristan of Nur? or the Bimaristan of N?r al-D?n Şeh?d, was also known as “B?m?ristan-ı ‘At?q” because a second bimaristan named Ergûn Kâmil was built in the city later on. In this bimaristan, patients were treated free of charge and their medication costs were covered by the waqf budget. In this study, after providing information about bimaristans, the Bimaristan of N?r? and its founder N?r al-D?n Zangi, the waqf assets of the Bimaristan of N?r? and their income amounts in the Mid-16th century, the waqf and hospital staff, their salaries and other expense items of the waqf are emphasised. The main sources of this study, which aims to reveal the importance of bimaristans in general and the Bimaristan of N?r? in Aleppo in particular in terms of the history of medicine and architecture and its operating model, are the Aleppo awqaf registers in various funds with waqfs records in the Ottoman Archives. © 2024, Selim Hilmi Ozkan. All rights reserved.
16. Yüzyılın Ortalarında Halep Nurî Bimaristanı Vakfı
Keywords: Aleppo; bimaristan; dâr al-shifa; N?r al-D?n Zangi; waqf